Analisis Indikator Entomologi dan Sebaran Jentik Aedes aegypti pada Daerah Stratifikasi Endemisitas Demam Berdarah Dengue di Kota Jayapura: Analysis of Entomology Indicator and distribution of Aedes aegypti vector based on stratified Endemicity Areas of Dengue Hemorrhagic Fever (DHF) in Jayapura City - Hartati, Risda; Satoto, Tri Baskoro T.; Murhandarwati, Elsa Herdiana; Widawati, Mutiara (Aspirator, 2021)
Abstract. The incidence rate (IR) of Dengue Hemorrhagic Fever in Papua Province in 2017 was8.04 per 100,000 population, with a case fatality rate (CFR) of 1.12%. In 2016, the Health Office ofJayapura City declared six urban villages as high endemic areas, four urban villages as high sporadicareas, and ten villages as DHF-free areas from a total of 39 urban villages in Jayapura. This studyaims to analyze larval by House index [HI], Container index [CI], Breateu index (BI), and Maya index[MI] as well as the distribution of vector Ae. aegypti in endemic, sporadic and DHF-free areas inJayapura City. The design of this study was a cross-sectional study. This research was conducted fromJanuary to March 2019. Subjects (375 houses) were surveyed according to WHO guidelines basedon its endemicity stratification. Observations of mosquitos’ larvae were done using visual and singlelarvae methods. The result of this research showed that endemic areas had their HI, CI and BI as muchas 43.3%, 16.5%, and 90.0%, respectively, with density figure is six. Sporadic areas had their HI,CI and BI as much as 35.4%, 10.9%, and 57.5%, respectively, with density figure is five. DHF-freeareas had their HI, CI, and BI as much as 14.8%, 5.7%, and 35.2%, respectively, with density figureis five. The Maya index for endemic and sporadic areas was categorized as moderate, while DHF-freeareas were low. Abstrak. Angka incidence rate (IR) Demam Berdarah Dengue (DBD) Provinsi Papua tahun2017 adalah 8,04 per 100.000 penduduk, dengan case fatality rate (CFR) sebesar 1,12%.Pada tahun 2016 Dinas Kesehatan Kota Jayapura menetapkan 6 kelurahan sebagai daerahendemis tinggi, 4 kelurahan sebagai daerah sporadis tinggi dan 10 kampung sebagai daerahbebas DBD dari total 39 kelurahan yang ada di Kota Jayapura. Tujuan penelitian ini untukmenganalisis kepadatan jentik menggunakan House Index (HI), Container Index (CI), BreateuIndex (BI), dan Maya Index (MI) serta menganalisis sebaran jentik Ae.aegypti di daerahendemis, sporadis dan bebas DBD di Kota Jayapura. Penelitian dilakukan dari Januari-Maret2019 dengan menggunakan metode potong lintang. Subyek penelitian 375 rumah disurveimenurut pedoman WHO menurut stratifikasi endemisitasnya. Observasi jentik nyamukdengan metode visual dan single larvae. Hasil penelitian ini menunjukkan bahwa indeksentomologi daerah endemis dengan nilai HI 43,3%, CI 16,5%, BI 90,0% dengan Density Figure(DF) 6 (tinggi). Sporadis: HI 35,4%, CI 10,9%, BI 57,5%, dengan density figure 5. Bebas DBD HI14,8%, CI 5,7% dan BI 35,2% dengan DF 5 (sedang). Status MI kategori sedang pada daerahendemis dan sporadis dan MI rendah pada daerah bebas DBD.